Evaluating a Mobile Digital Therapeutic for Vasomotor and Behavioral Health Symptoms Among Women in Midlife: Randomized Controlled Trial - Jennifer Duffecy; Arfa Rehman; Scott Gorman; Yong Lin Huang; Heide Klumpp (JMIR mHealth and uHealth)
AbstractBackground:Objective:Methods:Results:F2,262PF1,131PF2,262Pt147PF2,96PF2,40Ptt49Pt48PF2,186PF2,62Ptt95Pt93PConclusions: